Analisis Kontribusi Pajak Parkir dalam Meningkatkan Pendapatan Asli Daerah pada Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Nurweni Nurweni; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research is a survey of the contribution of parking taxes in the city of Medan. The purpose of this study was to determine the level of parking tax contribution to the local revenue of Medan City. This research was analyzed using a qualitative descriptive method. The survey was conducted at the Regional Tax and Retribution Management Agency in Medan City. The results of the study show that parking tax contribution receipts in Medan City in 2018 reached IDR 22,209,803,703.00, in 2019 it reached IDR 26,567,809,962.00 and in 2020 it reached IDR 14,111,000,000.00. Based on an analysis of the level of contribution of parking tax revenue in Medan City, it can be said that it is quite capable of contributing to increasing Medan City regional revenue with the elaboration that occurred in 2018, namely the proportion of 1.7%. In 2019, the highest proportion occurred at 1.8%. In 2020 it will get the lowest proportion, namely only 1.3%. This also shows that the level of tax contributions that are parked to local revenue is still not getting the maximum abuse.